Lack of clarity in the definition of treatment-related mortality: pediatric acute leukemia and adult acute promyelocytic leukemia as examples (Perspectives) - Hrodek, Otto (Transfuze a hematologie dnes, 2012)
Treatment-related mortality (TRM) is important in acute lymphoblastic leukemia and acute myeloid leukemia (AML); however, little is known about how TRM is defined across trials. Two major problems are related to what constitutes treatment versus disease-related cause of death and to TRM attribution (for example, death because of infection or hemorrhage). To address the former, we conducted a systematic review of randomized therapeutic pediatric acute leukemia and adult/pediatric acute promyelocytic leukemia trials and any study type focused on TRM in pediatric acute leukemia. We described definitions used for TRM. Sixty-six studies were included. Few therapeutic pediatric acute lymphoblastic leukemia studies (2/32, 6.3%) provided definitions for TRM, whereas more therapeutic pediatric AML studies (6/9, 66.7%) provided definitions. There was great heterogeneity in TRM classification. The authors of most studies relied on deaths during induction or in remission to delineate whether a death was TRM. However, 44.4% of therapeutic AML studies used death within a specific time frame to delineate TRM. We suggest that a consistent approach to defining and determining attribution for TRM in acute leukemia is an important future goal. Harmonization of definitions across the age spectrum would allow comparisons between pediatric and adult studies.
Keywords: Child; akutní erytroblastická leukemie; Cause of Death; akutní promyelocytární leukemie; Adult; dospělí; akutní lymfatická leukemie; Leukemia, Promyelocytic, Acute; příčina smrti; Humans; lidé; Randomized Controlled Trials as Topic; Precursor Cell Lymphoblastic Leukemia-Lymphoma; dítě; randomizované kontrolované studie jako téma; Leukemia, Erythroblastic, Acute